Using Evolutionary Analyses to Refine Whole-Genome Sequence Match Criteria - Pightling, Arthur W.; Rand, Hugh; Pettengill, James (Frontiers in Microbiology, 2022)
Whole-genome sequence databases continue to grow. Collection times between samples are also growing, providing both a challenge for comparing recently collected sequence data to historical samples and an opportunity for evolutionary analyses that can be used to refine match criteria. We measured evolutionary rates for 27 Salmonella enterica serotypes and genomic diversities for 29 serotypes. Based upon these measurements, we propose updated conditions for determining whether genome sequences match, including an evolutionary rate of 2.37 single-nucleotide polymorphisms (SNPs) per year to be applied to all S. enterica serotypes and serotype-specific SNP thresholds that range from 5 to 25 SNPs.